2017
DOI: 10.7717/peerj.3423
|View full text |Cite
|
Sign up to set email alerts
|

Microbial bioenergetics of coral-algal interactions

Abstract: Human impacts are causing ecosystem phase shifts from coral- to algal-dominated reef systems on a global scale. As these ecosystems undergo transition, there is an increased incidence of coral-macroalgal interactions. Mounting evidence indicates that the outcome of these interaction events is, in part, governed by microbially mediated dynamics. The allocation of available energy through different trophic levels, including the microbial food web, determines the outcome of these interactions and ultimately shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
2
37
0
Order By: Relevance
“…Arrows indicate flow of feedback loop, linking microbial coral–algal interactions with increased macroalgae cover promoting macroalgae dominated regimes. Adapted from Roach et al ().…”
Section: Biology Of Macroalgae On Coral Reefsmentioning
confidence: 99%
“…Arrows indicate flow of feedback loop, linking microbial coral–algal interactions with increased macroalgae cover promoting macroalgae dominated regimes. Adapted from Roach et al ().…”
Section: Biology Of Macroalgae On Coral Reefsmentioning
confidence: 99%
“…Increased respiration in at least 7 2 7 one species of coral an hour after exposure to hypoxia has been reported, followed by respiration 7 2 8 decrease after longer exposure (Dodds et al, 2007). Many studies of the effects of hypoxia on 7 2 9 corals have used environmental conditions at less than 50% air saturation, more in line with the reef health due to rising temperatures, eutrophication and competition with fleshy macroalgae 7 3 7 (Barott et al, 2009;Haas et al, 2013b,a;Sugden, 2017;Roach et al, 2017;Gajdzik & DeCarlo, 7 3 8 2017; Breitburg et al, 2018;Nelson & Altieri, 2019). H 2 O 2 in excess has also been linked to 7 3 9 coral bleaching (Downs et al, 2002).…”
Section: 2mentioning
confidence: 99%
“…Furthermore, it will be important to address the role of microbes in these competitive interactions, since recent studies have identified the important roles played by microorganisms in mediating coral–algal interactions (Roach et al. ).…”
Section: Algal Reefs Vs Sponge Reefsmentioning
confidence: 99%
“…Looking forward, it will be imperative to address uncertainty in the outcomes of competitive interactions between non-bioeroding sponges and algae, particularly in regions where they co-occur in high abundance. Furthermore, it will be important to address the role of microbes in these competitive interactions, since recent studies have identified the important roles played by microorganisms in mediating coral-algal interactions (Roach et al 2017).…”
Section: Algal Reefs Vs Sponge Reefsmentioning
confidence: 99%